AD HOC SURVEYS: HOW TO MEASURE AND REPORT QUALITY METHODS (Epidemiology, Biostatistics, and Public Health, 2022)
Surveys need a clear report on adopted quality methods to support surveillance, research and to implement evidence-based health policies. Aim of this report is to provide a simple and practical tool to those interested in survey, like HIS or HES , suggesting the different aspects of the quality to be controlled. These are crucial to generate useful and reliable results that can help the monitoring of health policy in Europe. Starting from the wide literature available in the field, the various quality dimensions that should be documented in a quality report and support the published results are briefly presented. In this paper, the six dimensions of the quality are analysed, as well as the different steps necessary to implement a survey, with particular attention to the quality and taking account of the remarkable expertise in the field. Before starting the survey, as known, the planning of specific steps is required. Moreover, to improve quality, training and testing of personnel involved in the different sets (organization, data collection, data processing, and statistical analysis) are fundamental. The methods used and the results obtained need to be published.